Optimal Time Intervals between Pre-Operative Radiotherapy or Chemoradiotherapy and Surgery in Rectal Cancer? - Glimelius, Bengt (Frontiers in Oncology, 2014)
Background In rectal cancer therapy, radiotherapy or chemoradiotherapy (RT/CRT) is extensively used preoperatively to (i) decrease local recurrence risks, (ii) allow radical surgery in non-resectable tumours and (iii) increase the chances of sphincter-saving surgery or (iv) organ preservation. There is a growing interest among clinicians and scientists to prolong the interval from the RT/CRT to surgery to achieve maximal tumour regression and to diminish complications during surgery. Methods The pros and cons of delaying surgery depending upon the aim of the preoperative RT/CRT are critically evaluated. Results Depending upon the clinical situation, the need for a time interval prior to surgery to allow tumour regression varies. In the first and most common situation (i), no regression is needed and any delay beyond what is needed for the acute radiation reaction in surrounding tissues to wash out can potentially only be deleterious. After short-course RT (5Gyx5) with immediate surgery, the ideal time between the last radiation fraction is 2-5 days since a slightly longer interval appears to increase surgical complications. A delay beyond 4 weeks appears safe; it results in tumour regression including pathologic complete responses, but is not yet fully evaluated concerning oncologic outcome. Surgical complications do not appear to be influenced by the CRT-surgery interval within reasonable limits (about 4-12 weeks), but this has not been sufficiently explored. Maximum tumour regression may not be seen in rectal adenocarcinomas until after several months; thus, a longer than usual delay may be of benefit in well responding tumours if limited or no surgery is planned, as in (iii) or (iv), otherwise not. Conclusions A longer time interval is undoubtedly of benefit in some clinical situations but may be counterproductive in most situations.